Antiproliferative effects of sulphonamide carbonic anhydrase inhibitors C18, SLC-0111 and acetazolamide on bladder, glioblastoma and pancreatic cancer cell lines. (1st January 2022) - Mussi, Silvia; Rezzola, Sara; Chiodelli, Paola; Nocentini, Alessio; Supuran, Claudiu T.; Ronca, Roberto
Abstract: Carbonic anhydrase IX/XII (CA IX/XII), are cell-surface enzymes typically expressed by cancer cells as a form of adaptation to hypoxia and acidosis. It has been widely reported that these proteins play pivotal roles in cancer progression fostering cell migration, aggressiveness and resistance to first line chemo- and radiotherapies. CA IX has emerged as a promising target in cancer therapy and several approaches and families of compounds were characterised in the attempt to find optimal targeting by inhibiting of the high catalytic activity of the enzyme. In the present work, different cell lines representing glioblastoma, bladder and pancreatic cancer have been exploited to compare the inhibitory and antiproliferative effect of primary sulphonamide acetazolamide (AAZ), the Phase Ib/II clinical grade sulphonamide SLC-0111, and a membrane-impermeant positively charged, pyridinium-derivative (C18). New hints regarding the possibility to exploit CA inhibitors in these cancer types are proposed.